Diagnostic accuracy of the Coopscore© to predict liver fibrosis in human immunodeficiency virus/hepatitis B virus co-infection. (March 2018) - Taibi, Ludmia; Boyd, Anders; Bosselut, Nelly; Bottero, Julie; Guéchot, Jérôme; Lacombe, Karine; Lasnier, Elisabeth; Baudin, Bruno; Vaubourdolle, Michel
Background: Non-invasive methods for assessing liver fibrosis are increasingly used as an alternative to liver biopsy. Recently, a score-based biochemical blood test (Coopscore © ) was developed in a cohort of patients chronically infected with hepatitis C virus, showing higher diagnostic performances than Fibrometer®, Fibrotest®, Hepascore® and Fibroscan™. Here, we assess its performance in patients co-infected with the human immunodeficiency virus and hepatitis B virus. Methods: Ninety-seven human immunodeficiency virus/hepatitis B virus co-infected patients with liver biopsies were included from a previously described cohort. Histological fibrosis staging using METAVIR criteria was used as the reference. Coopscore ©, Fibrotest®, Fibrometer®, Hepascore® and Zeng score were computed and compared with the Coopscore© using the Obuchowski index and area under the receiving operator characteristic curves. Results: The distribution of liver fibrosis levels was as follows: F0–F1 ( n  = 42), F2 ( n  = 25), F3 ( n  = 15) and F4 ( n  = 15). The Obuchowski index was higher for Coopscore © (0.774) than Fibrometer® (0.668), Hepascore® (0.690) and Zeng scores (0.704) ( P  < 0.05), reflecting a better ability to discriminate between fibrosis stages. Similarly, when predicting significant fibrosis (≥F2), the AUROC was significantly greater for the Coopscore © (0.836) than the Hepascore® (0.727) and Zeng scores (0.746), but not for the Fibrotest® (0.778, P  = 0.14) or Fibrometer® (0.790, P  = 0.19). The Coopscore © did not show a higher capacity than other scores to predict advanced fibrosis (≥F3) or cirrhosis (F4). Conclusions: This study supports the diagnostic value of the Coospcore © in fibrosis staging among human immunodeficiency virus/hepatitis B virus co-infected patients, especially to predict significant fibrosis.